Two-dimensional gauge theories and quantum integrable systems - SHATASHVILI, SAMSON (My University, 2008)
In this paper the relation between 2d topological gauge theo ries and Bethe Ansatz equations is reviewed. 1 In addition we present some new results and clarifications. W e hope the relations discussed here are particular examples o f more general relations between quantum topological fields theories in dimensions d ? 4 and quantum integrable systems
PUBLISHED
Keywords: Bethe Ansatz equations